Optimalisasi Karakter Berpikir Kritis Santri melalui Internalisasi Nilai Kepekaan Sosial di Pondok Pesantren Raudlatul Hanan, Kanigoro, Blitar - Cindya Alfi; Mohamad Fatih; Fernadiksa Rastra Putra Pratama; Trio Arista; Latifatul Jannah; Yunita Wulan Sari (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
In the era of information and globalization, critical thinking skills have become an essential competence for children, including students in Islamic boarding schools. These skills include the ability to ask questions, seek and evaluate evidence, compare alternatives, and solve problems logically. Islamic boarding schools inherently provide a disciplined environment grounded in religious values that supports the development of critical thinking. However, observations at Raudlatul Hanan Islamic Boarding School reveal several challenges, such as low social sensitivity, limited constructive conflict resolution, and the absence of consistent critical thinking habits. These conditions have the potential to hinder students’ adaptability and problem-solving abilities in the future. To address these issues, a program entitled “Optimizing Children’s Critical Thinking Character through the Internalization of Socio-Environmental Sensitivity Values” was implemented using a Participatory Action Research (PAR) approach. This approach actively involved students, ustadz/ustadzah, and Islamic boarding school administrators from problem identification through planning, implementation, and reflection. The activities included character education seminars, critical discussions, group competitions, and interviews aimed at fostering social sensitivity, reducing exclusive attitudes, and strengthening critical thinking skills from an early age. The results indicate high and enthusiastic student participation throughout all activities, leading both students and administrators to hope that the program will be implemented sustainably on an annual basis.